Storage-induced mechanical changes of porcine lenses assessed with optical coherence elastography and inverse finite element modeling - Tahsini, Vahoura; Gil, Iulen Cabeza; Kling, Sabine (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: In an effort of gaining a better understanding of the lens mechanics, ex vivo lenses samples are often used. Yet, ex vivo tissue might undergo important postmortem changes depending on the unavoidable preservation method employed. The purpose of this study was to assess how various storage conditions and the removal of the lens capsule affect the mechanical properties of ex vivo porcine lens samples. methods: A total of 81 freshly enucleated porcine eyes were obtained and divided into six groups and preserved differently. In the first three groups, the lens within the intact eye was preserved for 24h by: (i) freezing at -80°C (n=12), (ii) freezing at -20°C (n=12), and (iii) refrigeration at +8°C (n=12). In the remaining groups, the lenses were immediately extracted and treated as follows: (iv) kept intact, no storage (n=12), (v) decapsulated, no storage (n=21), and (vi) immersed in Minimum Essential Medium (MEM) at +8°C (n=12) for 24h. Frozen lenses were thawed at room temperature. Each lens was compressed between two glass lamellae and subjected, first to a period of relaxation during which the compression force was recorded and second to an oscillating micro-compression while the deformation was recorded with a total of 256 subsequent B-scans via optical coherence tomography. The corresponding axial strain was retrieved via phase-sensitive image processing and subsequently used as input for an inverse finite element analysis (iFEA) to retrieve the visco-hyperelastic material properties of the lenses. Results: After freezing at temperatures of -80°C and -20°C, the cortical strains increased by 14% (p=0.01) and 34% (p<0.001), and the nuclear strains decreased by 17% (p=0.014) and 36% (p<0.001), compared to the lenses tested immediately after postmortem, respectively. According to iFEA, this resulted from an increased ratio of the nuclear : cortical E-modulus (4.06 and 7.06) in -80°C and -20°C frozen lenses compared to fresh lenses (3.3). Decapsulation had the largest effect on the material constant C10, showing an increase both in the nucleus and cortex. Preservation of the intact eye in the refrigerator induced the least mechanical alterations in the lens, compared to the intact fresh condition.